Analysis of Factors Causing Cardiovascular Disorders in Adults Suffering from Hepatitis B and C within the Krobokan Community Health Center Area - Resa Nirmala Jona; Rusmiyati; Siti Juwariyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Hepatitis is an inflammatory disease of the liver caused by toxins or poisons originating from chemicals, drugs, or infectious agents such as viruses. Hepatitis can be suffered by all groups, from children to adults. Previous research has proven that hepatitis C infection also contributes to the development of metabolic disorders which play an important role as risk factors for cardiovascular disease and hypertension. The aim of this research is to determine the factors that cause cardiovascular disorders in adult hepatitis B and C sufferers. This research is a type of descriptive research with a cross sectional design. The research respondents were 36 people (aged 20-60 years) using simple random sampling technique. The research results showed that the majority of respondents were 51-60 years old (44.5%), had at least elementary school education (52.8%), male gender (55.6%) and hepatitis B type (86.1%). The results of the analysis of factors causing cardiovascular disorders in hepatitis B and C sufferers were lifestyle, history of DM and high cholesterol with P<0.05. In further research, efforts can be made to increase knowledge of hepatitis B and C sufferers so that cardiovascular disorders such as hypertension, CAD and even heart failure do not occur